(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Río del Peñón Formation (Borrello, 1955 nom. subst. González y Bossi, 1986) forms the upper part of the late Paleozoic outcropping in the Río Blanco anticline (northwest Precordillera, La Rioja Province). This unit is predominantly composed of a thick (1270 m.) sandstone and mudstone sequence including thin levels of coal and scarce conglomerates (Scalabrini Ortiz, 1972; Scalabrini Ortiz and Arrondo, 1973; González and Bossi, 1986). These deposits represent a complex interfingering of shallow marine and fluvial deposits recording relative sea-level fluctuations during the Late Carboniferous-Early Permian. The Río del Peñón Formation overlies andesites and volcanic breccias of the Punta del Agua Formation (Fig. 1 and 2a). Despite well known Late Carboniferous glacigenic deposits from different localities within the Precordillera (López Gamundí, 1987, 1997; López Gamundí and Martinez, 2000; Marenssi et al., 2004; Limarino and Spalletti, 2006; Henry et al., in press), glaciogenic deposits have not been reported from the Río del Peñón Formation. This documentation of glacial-related sediments in this succession serves to further constrain our knowledge of the temporal and paleogeographic distribution of Gondwanan glacial deposits.